PIZZA ENRIQUECIDA COM FIBRAS PARA PESSOAS COM DIVERTICULOSE - FROZZA, J.; PENTEADO, T.P.S.; CAVASSIN, T.A.; BORGES, J.N. (Visão Acadêmica, 2002)
A alimentação pobre em fibras determina cada vez mais o aparecimento de distúrbios gastrointestinais, como a diverticulose, os quais por modificações dietéticas planejadas podem aliviar seus sintomas, corrigir deficiências nutricionais e, quando possível, remeter à causa primária da patologia. Entre os alimentos processados ricos em fibras estão as farinhas, pães, biscoitos, bolos, pizzas; importantes componentes na dieta habitual da população brasileira e que podem ser adequados as necessidades de pessoas com diverticulose. Dez formulações tipo pizza foram testadas e duas selecionadas (F) contendo farelos de aveia e de trigo, em proporções iguais de 9,5%, (I) e farelo de aveia e farinha de trigo integral, em proporções iguais de 19,6%. Na avaliação sensorial dos protótipos, mais do que 85% dos 50 provadores não treinados responderam entre bom e muito bom numa escala hedônica de qualidade para os atributos: aspecto, sabor, maciez, umidade e teor de sal; confirmando a seleção da equipe de desenvolvimento. Além das características nutricionais dos protótipos selecionados (45g% de carboidratos, 9,5g% de proteínas e 5,4g% de lipídios), são de alto teor de fibras por atenderem a legislação vigente que determina o teor mínimo de 6 gramas de fibras por 100g do produto pronto para o consumo. Sob o aspecto tecnológico, emescala de desenvolvimento laboratorial, a pizza pronta para o consumo demonstrou ser viável quando observadas as diversas operações unitárias de processamento (mistura, amassamento, moldagem e assamento) e a vida de prateleira de 10 dias, sob refrigeração e sem uso de aditivos convencionais. PIZZA ENRICHED WITH STAPLE FIBERS FOR PEOPLE WITH DIVERTICULOSE Abstract The poor feeding in staple fibers of the current days the appearance of gastrointestinal riots determines each time more, which for planned dietary modifications can alleviate its symptoms, to correct deficiencies e, when possible; to send the cause primary of the pathology. Diverticulose is an anomaly of the normal function of the intestine; its symptoms and complications can hindered and/or be alleviated by the inclusion, in the diet, of alimentary staple fibers. It enters rich processed foods in staple fibers are flours, breads, biscuits, cakes, pizzas - the important components in the habitual diet of the Brazilian population and can be one opportunity to consumer, in special, to take care of the necessities of people with diverticulose. Ten preparations of pizza enriched with staple fiber sources were tested, two had been selected (F) brans of oats and wheat, in equal ratios of 9,5 %, and (I) bran of oats and flour of integral wheat, in equal ratios of 19,6%. The sensorial evaluation of the archetypes carried through by 50 trained cloth provers, indicate that more than 85% had answered between good and very good in a scale of quality for the attributes: aspect, flavor, smooth, humidity and text of salt; in order to confirm the election of the development team. Beyond the supplied nutrients by the archetypes selected in average of 45 g% of carbohydrates, 9,5 proteins g %, 5,4 g% of lipids, and of 7,2g% (f) and 6,1g% (I) of fibers; these products can be considered of hight staple fiber because the minimum legal is the of 6 grams of staple fibers for 100g of the ready product for the consumption. Under the technological aspect, in scale of laboratorial development, the ready pizza for the consumption - it demonstrated viable when to be observed the diverse unitárias operations of processing (mixture, kneading,molding and cooking) and the life of shelf of 10 days under refrigeration and without conventional additive use.